TAWARAN METODOLOGI FAZLUR RAHMAN DALAM TEOLOGI ISLAM - Harianto, Budi (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
Islamic intellectual treasures abundant, but very poor in methodology. Inespecially in the field of theology, was minimal in the use of a methodology, especially in the classical period and the medieval. The methodology in reviewing the new Islamic theology known and discussed in modern times. Islam has buildings that are monotheistic. A religion that has the confidence of the One God. However, the empirical reality, the one God gave birth to a range of views and theological concepts are different. This means that even God as the object of faith Muslims as the God, but when the same Lord responded and understood by many individual Muslims worldwide, it gave birth to a  variety of the concept of God. Differences theological views that depart from the diversity of logic, or form with paradigm, viewpoint and methodology used by the Muslims themselves in capturing and interpreting God. One party Islamic anyone using a logical perspective, ie, attempt to understand God through ratio.No more base through an intuitive understanding. On the other hand thereare quite satisfied with the text.]Keywords: Theology, methodology, Fazlur Rahman, Critical Method,Double Movement.